2011
DOI: 10.1159/000324214
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Voice Handicap Index as a Screening Tool in Dysphonic Patients

Abstract: Objective: The aim of the study was to assess the applicability of the Voice Handicap Index (VHI) in the screening diagnostics of voice dysfunction and in the evaluation of the level of handicap due to dysphonia. Patients andMethods: A total of 165 patients with voice disorders (vocal paresis, benign vocal fold masses, and functional dysphonia) and 65 healthy controls completed the VHI questionnaire. All the participants were subjected to maximum phonation time (MPT) assessment, the patients also to laryngovid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 26 publications
(14 reference statements)
5
22
0
3
Order By: Relevance
“…Simberg et al [32] reported that combining perceptual voice quality and vocal symptoms can effectively screen potential voice disorders among teachers and students. A study demonstrated that self-completed questionnaires (i.e., VHI) can be applied to distinguish between subjects with or without voice disorders [33]. By using DT modeling, a recent study showed that other demographic factors (e.g., age, occupation, and smoking status) are significant risk factors for voice disorders in the general population in addition to VHI and voice symptoms [34].…”
Section: Discussionmentioning
confidence: 99%
“…Simberg et al [32] reported that combining perceptual voice quality and vocal symptoms can effectively screen potential voice disorders among teachers and students. A study demonstrated that self-completed questionnaires (i.e., VHI) can be applied to distinguish between subjects with or without voice disorders [33]. By using DT modeling, a recent study showed that other demographic factors (e.g., age, occupation, and smoking status) are significant risk factors for voice disorders in the general population in addition to VHI and voice symptoms [34].…”
Section: Discussionmentioning
confidence: 99%
“…The VHI measure was used in this study as a reference tool, as it is a validated tool which has proven reliable in a number of studies on Polish population [18,19] and has been commonly used in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly used self-report questionnaires are the Voice Handicap Index (VHI), Voice Symptom Scale (VoiSS) and Voice Related Quality of Life (V-RQOL). In Polish clinical practice, among phoniatricians, otolaryngologists and speech therapists the VHI has been so far the only such a tool used for monitoring occupational voice [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…43 However, one study reported poor predictive values for voice problems in teachers with VHI-10. 44 VHI has been shown to be a good screening tool, 45 and it is distinct from, and complements, acoustic analysis of voice. 46,47 Ideally, an annual screen could incorporate an automated acoustic analysis, although there are problems with deciding which parameters are important and relevant and which best correlate with the gold standards of perceptual voice analysis by GRBAS or CAPE-V.…”
Section: Discussionmentioning
confidence: 99%